Nick Ringo III - Sahl, Ted (photographer):::Creator::::::::::::
Photograph show Nick Ringo III sitting on the floor with a racing helmet at his feet. He is wearing racing gear and is sitting with his right leg bent up and supporting his right arm. The other leg is bent and resting completely on the floor. His racing suit reads "Nick Ringo III" and "Simpso[n] Race [illegible]".